Immortalization and neoplastic transformation of normal diploid cells by defined cloned DNA fragments of herpes simplex virus type 2. - Jariwalla, R J (1983)
Diploid Syrian hamster embryo (SHE) cells were passaged after transfection with recombinant plasmids containing herpes simplex virus type 2 (HSV-2) DNA inserts Bgl II focus-forming fragment N, Bgl II transforming fragment C, and EcoRI/HindIII fragment AE. Cultures transfected with salmon DNA or with 0.1-5.0 micrograms of Bgl II fragment N reached crisis and senesced. Those transfected with 0.1-0.5 micrograms of Bgl II fragment C or its left-hand 64% subclone EcoRI/HindIII fragment AE escaped senescence and formed continuous lines. At early passages, these lines as well as isolated clones grew in 2% serum but formed small (less than or equal to 0.1 mm) colonies in 0.3% agarose and were nontumorigenic. Serial passaging of Bgl II fragment C-induced cultures and isolated clones resulted in the appearance of large (greater than 0.25 mm) colonies in agarose followed by tumorigenicity. This behavior was not exhibited by the EcoRI/HindIII fragment AE-induced cultures that remained nontumorigenic after 53 passages. DNA from normal SHE cells exhibited homology to Bgl II fragment C but, under relatively stringent conditions, DNAs from transformed and tumor-derived lines exhibited discrete hybridizing bands comigrating with authentic viral fragments. These results indicate that neoplastic transformation of normal diploid SHE cells by HSV-2 DNA fragments involves at least two distinct steps--i.e., immortalization and conversion to tumorigenicity. EcoRI/HindIII fragment AE representing the left 64% of Bgl II fragment C is sufficient to induce immortalization. However, DNA sequences from both left-hand 64% and right-hand 36% subfragments of Bgl II fragment C are required for tumorigenic transformation.